Syntheses and luminescent properties of tetrahedral nickel(0) complexes - Frem, Regina Célia Galvão [UNESP]; Massabni, Antonio Carlos [UNESP]; Massabni, A. M G [UNESP]; Mauro, Antonio Eduardo [UNESP] (Elsevier, 1997)
Tetrahedral nickel(0) complexes [NiL4], [Ni(dppe)2] and [Ni(CO)2(SbPh3)2] (L=AsPh3, SbPh3, P(OPh)3, dppe=1,2-bis(diphenylphosphino)ethane) were prepared by reduction of NiCl2·6H2O with NaBH4 under N2 or CO atmosphere in the presence of the ligand. The complex [Ni(SbPh3)4] was also obtained by electrolysis at -1.3 V (Ag/Ag+), under a platinum gauze, of the system NiCl2·6H2O/SbPh3 (molar ratio=1:4). These complexes, both in the solid state and in solution, show an orange emission at room temperature, when excited with UV radiation. A qualitative molecular orbital diagram for the [NiL4] complexes is proposed. Electronic absorption spectra of the complexes show bands near 400 nm assigned as MLCT π*2e←d2t2. A 1A1←3T1 transition is suggested for the emission observed in these systems. Lifetimes in microsecond range were estimated from time-resolved emission spectra. Spectroscopic properties of the free ligands have also been investigated.
Keywords: Electronic absorption; Nickel(0) complexes; Photophysics